1980
DOI: 10.1037/0012-1649.16.6.555
|View full text |Cite
|
Sign up to set email alerts
|

Distributive justice development and social class.

Abstract: Two studies were undertaken to assess distributive justice development in lower-and middle-class children attending social-class-integrated schools.In Study 1, 28 middle-and 28 lower-class white children from kindergarten and third grade were given the Distributive Justice Scale and a vocabulary test. Results showed that regardless of grade, the lower class lagged behind the middle class in distributive justice development even when vocabulary was controlled. In Study 2, 32 middle-and 32 lower-class black chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
6
0
1

Year Published

1981
1981
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 29 publications
3
6
0
1
Order By: Relevance
“…In line with previous research (Enright et al, 1980a;Nisan, 1984;Mann et al, 1985), we found a difference in the predicted direction between Indonesian and New Zealand children. New Zealand 7-year-olds were more likely to make use of the equity rule in their distributional behaviour.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In line with previous research (Enright et al, 1980a;Nisan, 1984;Mann et al, 1985), we found a difference in the predicted direction between Indonesian and New Zealand children. New Zealand 7-year-olds were more likely to make use of the equity rule in their distributional behaviour.…”
Section: Discussionsupporting
confidence: 93%
“…For example, the order of emergence of different stages appeared to be quite similar across US, Swedish, and Zaı¨rean samples (Enright et al, 1980b(Enright et al, , 1984, although emergence is slower in children from US working rather than US middle class backgrounds (Enright et al, 1980a). Sigelman and Waitzman (1991) found older children to be more flexible and sensitive to context.…”
mentioning
confidence: 95%
“…The sociometric findings from the Enright, Enright, Manheim, and Harris (1980) midwest study were replicated here with one exception. In the former sample, it was not until third grade that middle-and lowerclass children agreed that lower-class individuals possessed more negative traits than middle-class children did.…”
Section: Discussionsupporting
confidence: 51%
“…Fifty-six subjects participated (seven lower-class and seven middle-class males, and seven lower-class and seven middle-class females from both kindergarten and third grade). This sample, composed of all white children, was drawn 1 year later from the same school in southern Florida as the sample in Enright, Enright, Manheim, & Harris (1980). The new sample represented not a longitudinal but another cross-sectional design.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation